Mazhab dan Istimbath Hukum - Jidan Ahmad Fadillah; Jusuf Satriani; Mohamad Badrus; Iffatin Nur (Universitas Muhammadiyah Surabaya, 2021)
Abstract This article aims to explain the position of fiqh schools in Islamic law and. Many problems arise because of a lack of understanding of mazhab issues, such as taqlid attitudes, school fanaticism, and opinions about obligations to certain schools. As a result, due to different schools of thought, there was strife within Muslims. Even more extreme, because it is different from the Madzhab or the teachings of its ulama, the Koran and Hadith are rejected. The schools appeared after the third period of the initial generation, namely in the second century Hijriah and this period is called the Mujahideen period. Every school, like Shafi’i, Hanafi, Maliki and Hambali have their own uniqueness. The uniqueness lies in the methods and applications of the Istinbath law which are used of each school and the basis used. Such as Imam Syafi’i has a different method with the other mazhab priests in establishing the law, which greatly emphasizes Sunnah, nash, and ra’yu. In addition, in establishing the Shafi’i faith law has two opinions known as Qaul Qadim and Qaul Jadid. This study examines the faoundations of the scholars in performing ijtihad and istinbath methods of law. Keywords: madzhab, istimbath, and law.